How getting noticed helps getting on: successful attention capture doubles children's cooperative play - Yuill, Nicola; Hinske, Steve; Williams, Sophie E.; Leith, Georgia (Frontiers in Psychology, 2014)
Cooperative social interaction is a complex skill that involves maintaining shared attention and continually negotiating a common frame of reference. Privileged in human evolution, cooperation provides support for the development of social-cognitive skills. We hypothesise that providing audio support for capturing playmates’ attention will increase cooperative play in groups of young children. Attention capture was manipulated via an audio-augmented toy to boost children’s attention bids. Study 1 (48 6- to 11-year-olds) showed that the augmented toy yielded significantly more cooperative play in triads compared to the same toy without augmentation. In Study 2 (33 7- to 9-year-olds) the augmented toy supported greater success of attention bids which were associated with longer cooperative play, associated in turn with better group narratives. The results show how cooperation requires moment-by-moment coordination of attention and how we can manipulate environments to reveal and support mechanisms of social interaction. Our findings have implications for understanding the role of joint attention in the development of cooperative action and shared understanding.